1999
DOI: 10.1046/j.1365-2591.1999.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Crown cementation and pulpal health

Abstract: A direct result of the liquid continuum within the pulpo-dentine complex is the effect of restorative dentistry on the health of the dental pulp. Better understanding of the role of the complex in relation to restorative dentistry enables strategies to be devised in preserving pulp vitality. A review of the literature produced good laboratory evidence to support the prophylactic sealing of crown preparations with dentine bonding agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…18 The assumption that adhesive-sealed dentine is impermeable to water movement has resulted in the effective use of single-bottle total-etch adhesives in reducing cervical hypersensitivity via resin-obliteration of exposed dentinal tubules. [19][20][21][22] Likewise, sealing of tooth preparations for indirect restorations with dentine adhesives has been advocated in fixed prosthodontics that involves the preparation of vital teeth [23][24][25][26] , since the use of provisional cements may permit more microleakage of bacteria and their products than the final restorations. 27,28 In view of the increased adhesive permeability associated with simplified-step adhesives, it is not known whether a hermetic seal can be achieved with the use of single-bottle totaletch adhesives for the sealing of preparations for indirect restorations in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…18 The assumption that adhesive-sealed dentine is impermeable to water movement has resulted in the effective use of single-bottle total-etch adhesives in reducing cervical hypersensitivity via resin-obliteration of exposed dentinal tubules. [19][20][21][22] Likewise, sealing of tooth preparations for indirect restorations with dentine adhesives has been advocated in fixed prosthodontics that involves the preparation of vital teeth [23][24][25][26] , since the use of provisional cements may permit more microleakage of bacteria and their products than the final restorations. 27,28 In view of the increased adhesive permeability associated with simplified-step adhesives, it is not known whether a hermetic seal can be achieved with the use of single-bottle totaletch adhesives for the sealing of preparations for indirect restorations in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, dentists were split as to the value of a resin‐bonding agent, with 23% considering it “very important” and 31% considering it “not important.” It seems logical that resin impregnation might reduce sensitivity, and several authors have advocated its use 26 . However, although case reports have extolled this technique's effectiveness, 27 a clinical trial did not demonstrate its effectiveness, 23 nor has it been found to reduce sensitivity with amalgam restoration placement 28–30 .…”
Section: Discussionmentioning
confidence: 99%
“…These values were transformed to number from 0 (nonsensitive) to 10 (extremely hypersensitive). 12 Evaluation of postcementation sensitivity level: The patient's response to sensitivity was evaluated immediately after 5-minute postcementation, 1-day postcementation, 1-week postcementation at routine recall visits. All individual patient data forms and a summary spreadsheet of the results were thoroughly examined and data was statistically analyzed.…”
Section: Patient Evaluation Proceduresmentioning
confidence: 99%
“…It has been demonstrated that dentin permeability (ability of the fluid to shift across dentin) increases as dentin is prepared closer to pulp, hence it should be covered with materials that are biologically compatible with the pulp and will seal the dentin well. 11,12 Sealing of dentine with bonding agent or desensitizing agent was suggested following tooth preparation and before making impression. 18 The thin film of these agents decreases the dentin permeability and would also prevent hydraulic fluid movement during impression making and during final luting of the restorations.…”
mentioning
confidence: 99%